Eugenol apresenta efeito antidepressivo em modelo in vivo em camundongos: análises comportamentais, neuroquímicas e moleculares. - Aragão, Paulo de Tarso Teles Dourado de (2024)
Depression is the most frequent psychosomatic illness in today's society, reaching approximately 322 million cases by 2017. This disorder has no yet fully elucidated, but major theories about Depression involve intracellular molecular irregularity that interact with environmental and genetics pre-provisions. To the initial pathological treatments, drugs from popular knowledge was made using plants, but researches with biocomposites with proven antidepressant activity are still scarce. Eugenol (4-allyl-1-hydroxy-2- methoxybenzene) has wide pharmacological activity and has harmacokinetic characteristics relevant for neurological studies because it has low molecular weight, high liposolubility and low toxicity. For this study, male adult mice weighing 25 to 30 grams were used, which were submitted to the behavioral tests of Forced swimming, Tail Suspension, Open Field, Plus Maze and Object Recognition. For neurochemical and molecular tests, brain areas were used, namely: Frontal Cortex, Hippocampus and Striatum of animals duly euthanized by cervical dislocation. The neurochemical test used was the dosage of Glutathione, TBARS and nitrite/nitrate. The results showed that Eugenol, only at its lowest dose, increased the locomotor activity and the number of vertical exploratory activities and decreased the animals' standing time. In the other variables evaluated in the open field test Eugenol was not able to change any of the parameters. In the high cross maze test, in no dose Eugenol altered the data obtained, showing no anxiolytic or anxiogenic effect. In the Tail Suspension and Forced Swim tests, the 50 mg / kg dose obtained better results than the standard antidepressant drug, showing its antidepressant activity. In memory-related tests, the 25 mg / kg dose was the only dose that differed from the vehicle. Regarding the dosage of Glutathione, only the dose of 25mg / kg was different in relation to the control, increasing its levels both in the hippocampus and in the striatum and prefrontal cortex. Analyzing TBARS, the Eugenol reduce the levels of MDA in the hippocampus and cortex. Nitrite and Nitrate levels has no significant difference when analyze Eugenol and the negative controls. It was possible to observe through molecular docking the binding of Eugenol to proteins with involvement in depression, such as the serotonin 2A receptor and cyclo-oxidase 2. These data suggest an antidepressant activity of Eugenol at the doses tested and also neuroprotective effects, being a possible and effective compound for treatment for Depression.